A distributed Wireless Sensor Network testbed with energy consumption estimation. (2nd August 2010) - Sheu, Jang-Ping; Chang, Chia-Chi; Yang, Wei-Sheng
In this paper, we design and implement a WSN testbed with a distributed architecture. It allows researchers to submit their experiments and to retrieve the results from the central server. In the testbed, we also propose a software-based hardware-supported scheme to measure the energy consumption of running sensor nodes. And we compare our energy-consumption estimation with oscilloscope measurements. The results show that the energy consumption is very close to oscilloscope measurements.